Crisis-tested Europe — Towards a Patchwork Union? - Heinz Handler (Wirtschaftsdienst)
Abstract Based on an insufficiently consolidated “European identity”, the European Union has recently been exposed to the challenges of globalisation, financial disturbances, migration and populistic nationalism, Brexit, and the COVID 19 virus. The negative consequences of these somehow interrelated phenomena have to some extent been kept in check but are likely to be dwarfed by the looming threat of climate change. The present analysis underlines the added value of European integration, but also dampens illusions about the future of the Union. Although the crises seem to have strengthened the solidarity among the core of the EU, differences between member states have also become more apparent, as exemplified by the Brexit. The goal of a full-fledged political union is now a long way off, and it is therefore worth aiming for secondbest solutions, such as some form of differentiated further integration. The ongoing Conference on the Future of Europe offers the opportunity for an evaluation of such concepts.